Mechanisms of synchronization of relativistic electron bunches at wakefield excitation in plasma - Lotov, K.V.; Maslov, V.I.; Onishchenko, I.N.; Yarovaya, I.P. (Вопросы атомной науки и техники, 2013)
Using code Lcode the mechanisms of defocusing of electron bunches at wakefield excitation in plasma have been demonstrated. Використовуючи код Lcode, продемонстровані механізми дефокусування електронних згустків при збудженні кільватерного поля в плазмі. Используя код Lcode, продемонстрированы механизмы дефокусировки электронных сгустков при возбуждении кильватерного поля в плазме.